2008
DOI: 10.1590/s1676-06032008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Nicho ecológico e aspectos da história natural de Phyllomedusa azurea (Anura: Hylidae, Phyllomedusinae) no Cerrado do Brasil Central

Abstract: Ecological niche and aspects of the natural history of Phyllomedusa azurea (Anura: Hylidae, Phyllomedusinae) in the Cerrado of Central Brazil. Biota Neotrop. 8(4): http://www.biotaneotropica. org.br/v8n4/en/abstract?article+bn02108042008Abstract: Aspects of the ecology and natural history of Phyllomedusa azurea were investigated in an area of Central Brazilian Cerrado between April, 2006, and February, 2007. Observations were conducted between 6:00 PM and 5:00 AM. The study focused on spatial, temporal, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
2
11
1
3
Order By: Relevance
“…The mean snout-vent length of the three collected males (35.7 + 1.78 mm; Table 1) was slightly inferior to the means presented by Caramaschi (2007Caramaschi ( "2006 37.7 mm) and Freitas et al (2008;36.45 mm), but is still included between the extreme values recorded by these authors. All the measurements of P. azurea taken in this study corroborate those of Caramaschi (2007Caramaschi ( "2006 and Freitas et al (2008), except by the head length that was slightly inferior to the values recorded by Caramaschi (2007Caramaschi ( "2006 If we consider the location of the most recent records for this species in north (Calderon et al 2009) and south (this paper), as well as the morphologic differences observed in the pictures presented by those authors, we cannot discard the hypothesis that P. azurea could be in reality a species complex. However, only a widest review could solve this question, and this is not the purpose of this paper.…”
contrasting
confidence: 57%
See 4 more Smart Citations
“…The mean snout-vent length of the three collected males (35.7 + 1.78 mm; Table 1) was slightly inferior to the means presented by Caramaschi (2007Caramaschi ( "2006 37.7 mm) and Freitas et al (2008;36.45 mm), but is still included between the extreme values recorded by these authors. All the measurements of P. azurea taken in this study corroborate those of Caramaschi (2007Caramaschi ( "2006 and Freitas et al (2008), except by the head length that was slightly inferior to the values recorded by Caramaschi (2007Caramaschi ( "2006 If we consider the location of the most recent records for this species in north (Calderon et al 2009) and south (this paper), as well as the morphologic differences observed in the pictures presented by those authors, we cannot discard the hypothesis that P. azurea could be in reality a species complex. However, only a widest review could solve this question, and this is not the purpose of this paper.…”
contrasting
confidence: 57%
“…The landscape is mainly constituted by native grasslands, but also includes swampy areas and patches of mixed ombrophilous forest (Bencke et al 2006). This distribution extension represents the first record of P. azurea outside the savanna type formations of Cerrado, Pantanal and Chaco biomes, where the species had been previously recorded (Caramaschi 2007(Caramaschi "2006Prado et al 2008;Freitas et al 2008;Frost 2009;Calderon et al 2009). The physiognomic vegetation of the area is very similar to other planaltic fields in southern Brazil ("Campos de Cima da Serra" in northeastern state of Rio Grande do Sul and "Campos do Planalto das Araucárias" in southeastern state of Santa Catarina) (Bencke et al 2006) considered as inside Campos Sulinos biome (MMA 2000).…”
supporting
confidence: 52%
See 3 more Smart Citations